Photodynamic therapy in the treatment of denture stomatitis: A systematic review and meta-analysis - Vila-Nova, Taciana Emília Leite; Leão, Rafaella de Souza; Santiago Junior, Joel Ferreira; Pellizzer, Eduardo Piza [UNESP]; Vasconcelos, Belmiro Cavalcanti do Egito; Moraes, Sandra Lúcia Dantas (Elsevier, 2022)
Statement of problem: Photodynamic therapy is widely used in dentistry, but limited evidence exists regarding its effectiveness in treating denture stomatitis. High resistance to antifungals has been reported, and photodynamic therapy could be an alternative treatment. Purpose: The purpose of this systematic review and meta-analysis was to evaluate whether photodynamic therapy is effective in reducing denture stomatitis. Material and methods: A systematic review was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist and recorded in the prospective register of systematic reviews (PROSPERO) (CRD42020205589) to answer the population, intervention, control, outcome (PICO) question: “Is photodynamic therapy effective in the treatment of denture stomatitis when compared with the use of antifungal agents?” Electronic searches were performed in databases PubMed/MEDLINE, Cochrane library, and Web of Science for articles published until February 2021 by using the following terms: (denture stomatitis OR oral candidiasis) AND (low-level light therapy OR laser therapy OR lasers OR photodynamic therapies OR photochemotherapy) AND (antifungal drugs OR antifungal agents OR antimicrobial OR treatment). Clinical trials and randomized clinical trials, studies in the English language, and studies comparing antifungal agents with photodynamic therapy were included. Results: In total, 5 articles were selected for the qualitative analysis and 3 for the meta-analysis. No significant difference was detected between antifungal therapy and photodynamic therapy in the reduction of colony-forming units on the palate. In a subgroup analysis, a significant difference was found in the reduction of colony-forming units on the palate at 15 days and at the denture surface at 30 days. Conclusions: Photodynamic therapy is effective in the treatment of denture stomatitis, but after 30 days and 15 days, the antifungals demonstrated better performance.